Evaluation Of The Control And Prevention Of The Spread Of Corona Virus Disease (Covid-19) At Tigaras Port In 2021 - Driaskoro Budi Sidharta; Dahlia Dewi A; Maria Hygeia Faperina Marpaung (IWJ : Inland Waterways Journal, 2021)
Tigaras Port is managed by the North Sumatra Region II Land Transportation Management Center. Vessels operating at this port consist of 2 motorized crossing ships, namely KMP. North Sumatra I and KMP. North Sumatra II, as well as 17 traditional motor boats. Tigaras Port is one of the ports that has a busy trip schedule and is crowded with visitors every day. The world is currently being hit by a disease epidemic due to Corona Virus Disease (Covid-19) and the epidemic has had a major impact, including to the transportation sector. However, there is no maximum control effort and the level of compliance with the application of health protocols at Tigaras port, both from the passenger sector, transportation facilities operators, and transportation infrastructure operators is still very minimal.